IMPLEMENTATION OF ISAK 35 IN THE PREPARATION OF FINANCIAL STATEMENTS AT DARUSSALAM ISLAMIC BOARDING SCHOOL JOMBANG - Purwanto, Wahyu Hadi; Djalaludin, Ahmad (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
A non-profit organization mainly focuses on service without the intention of getting maximum profit. Islamic boarding school foundations are organizations engaged in education, so educational foundations are a part of non-profit entities. As a non-profit entity, the foundation must have clarity on acquiring resources and financial management to increase accountability to donors and several parties. This study aims to find out how to present and compile financial statements at Darussalam Islamic Boarding School Jombang with the concept of ISAK 35. The types of data used are primary data and secondary data. Data collection techniques are using interviews and documentation, which is directly researched at the research location, and looking for data that suits the needs of this study, both primary and secondary data. The result of this study is the form of financial statements at the Darussalam Islamic Boarding School Jombang in 2022, which has adjusted to the ISAK 35 concept, consisting of a Comprehensive Income Statement, Cash Flow Statement, Net Asset Change Report, Financial Position Statement, and Notes to Financial Statements. The presentation of Financial Statements based on ISAK 35 serves to make it easier for interested parties to read how the financial statements are to complete the elements of financial statements and make it easier to find out the surplus (deficit) of Islamic boarding school assets in every year, and it also essential to decide in the following years.